Features of Clinical and Laboratory Parameters in Children with Arthritis, which Have Increased Antibody Titers to Cyclic Citrullinated Peptide and Modified Citrullinated Vimentin - I.S. Lebets; N.O. Panko (Zaslavsky O.Yu., 2013)
77 children with inflammatory lesions of the joints have been examined in the study. The characteristics of clinical signs and laboratory parameters in patients with arthritis, who have increased antibody titers to cyclic citrullinated peptide (a-CCP) and modified citrullinated vimentin (a-MCV) are presented. The patients with juvenile rheumatoid arthritis which a-CCP positive were adolescents, they had polyarticular lesions, a significant number of active joints, and the trend to more rapid development of radiologic stage III by Steinbrocker. Positivity for a-MCV was often detected from an early age, but not only in patients with juvenile rheumatoid arthritis. These patients were seronegative for rheumatoid factor, high frequency of involvement of the knee joints with their swelling. Radiological changes in joints of these patients seldom exceeded II stage by Steinbrocker.